Arte letteraria e coerenza filosofica: il sole, la linea e la caverna - Motta, Anna (Peitho. Examina Antiqua, 2024)
The approach I propose here to Books VI and VII of Plato’s Republic is to offer some reflections on the organicist and perspectivist readings. Perspectivism seems in some respects to be a variant of organicism. Indeed, both approaches allow for a reassessment not only of the various parts that make up a dialogue, but also, more generally, of the importance of the literary or dramatic form, which is marginalised by the evolutionist reading. The aim of this essay is therefore to try to understand some of the images present in the central books of the Republic, without burdening them with theoretical structures and questionable chronologies, but rather by noting their importance in the overall design of the individual text and their consistence within a broader organism, the entire and unitary Platonic corpus of dialogues. To this end, I will try to highlight the subtle differences between organicism and perspectivism. I will focus on the relationship between literary constructions and theoretical speculations that make the Republic an organically unified text in itself and perfectly consistent with the entire corpus of dialogues. Three images in particular will help me to show how literature and philosophy meet: the sun analogy, the divided line and the allegory of the cave. My aim is not to say what exactly the epistemology of the central books of the Republic consists in, but rather to try to identify the pitfalls in the text when philosophical questions about epistemological issues are separated from literary ones.